2014
DOI: 10.1007/s10096-014-2262-0
|View full text |Cite
|
Sign up to set email alerts
|

Automated liquid culture system misses isoniazid heteroresistance in Mycobacterium tuberculosis isolates with mutations in the promoter region of the inhA gene

Abstract: Heteroresistance in Mycobacterium tuberculosis isolates remains the major challenge for phenotypic drug susceptibility testing (DST) methods to detect drug resistance. The aim of this study was to investigate the abilities of phenotypic DST methods to identify the isoniazid (INH) heteroresistance in M. tuberculosis. We found that the broth dilution method was able to detect INH resistance if 0.5 % resistant bacteria with mutations in the katG and oxyR-ahpC regions were present, while the detection limit ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Indirect drug susceptibility of the culture-positive isolates identified as MTB was detected by the Bactec MGIT 960 automated system according to the manufacturer’s instructions. The critical concentrations were 1.0 μg/mL for rifampicin (RIF), 0.1 μg/ml for isoniazid (INH), 2 μg/mL for ofloxacin(OFLX), 0.5 μg/mL for amikacin (AMK), and 1.0 μg/mL for kanamycin (KAN) 27 32 33 . The clinical TB laboratories enrolled in this study have passed the proficiency testing for conventional DST organized by the National TB Reference Laboratory of the China CDC.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect drug susceptibility of the culture-positive isolates identified as MTB was detected by the Bactec MGIT 960 automated system according to the manufacturer’s instructions. The critical concentrations were 1.0 μg/mL for rifampicin (RIF), 0.1 μg/ml for isoniazid (INH), 2 μg/mL for ofloxacin(OFLX), 0.5 μg/mL for amikacin (AMK), and 1.0 μg/mL for kanamycin (KAN) 27 32 33 . The clinical TB laboratories enrolled in this study have passed the proficiency testing for conventional DST organized by the National TB Reference Laboratory of the China CDC.…”
Section: Methodsmentioning
confidence: 99%
“…The range in the abilities for drug-resistant TB detection among these studies may be explained by the differences in the molecular characteristics of predominant drug-resistant MTB strains that exist across different regions. In addition, heteroresistance is considered an important mechanism in the emergence of drug resistance 21,22. However, the HAIN test could not detect minor drug-resistant populations from tubercle bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-culturing of isolates for MB7H10 and MYCTB plate DST may have caused changes in the sample strain population from the original sample used for DST in presence of hetero-resistance [ 18 ]. Studies have indicated hero-resistance to affect DST results from the sub-cultured strains [ 19 , 20 ], however, this is expected to be minimal given the low prevalence of hetero-resistance. This is one of the few studies which have compared LJ and MB7H10 DST with MYCOTB plate and our findings are vital for future studies and recommendations.…”
Section: Discussionmentioning
confidence: 99%